2002
DOI: 10.1002/ajhb.10049
|View full text |Cite
|
Sign up to set email alerts
|

Use of surnames for a demo‐ecological analysis: A study in southwest Sardinia

Abstract: This study used surnames collected in 12 municipalities of Sulcis, a historic-geographical region located in southwest Sardinia (Italy). An ecological index of similarity was drawn as the main analysis. The distribution of surnames was also used to determine the diversity of municipality populations by using another ecological index. Two municipalities have a high percentage of Genoese surnames and this element reflects a specific history and culture, different from other Sardinian localities. These peculiarit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…In all the topological representations of Sardinia, Carloforte is not included in the main Sardinian cluster since its inhabitants have Ligurian origins and they settled in Sardinia in the 18th century, coming from the island of Tabarka in north-western Tunisia (Vallebona, 1988). The structure of surnames in Carloforte is still rather peculiar, and very different from that of the other Sardinian municipalities (Vona et al, 1996;Caravello & Tasso, 2002b). Carbonia, another Sardinian municipality not far from Carloforte (Fig.…”
Section: Discussionmentioning
confidence: 84%
“…In all the topological representations of Sardinia, Carloforte is not included in the main Sardinian cluster since its inhabitants have Ligurian origins and they settled in Sardinia in the 18th century, coming from the island of Tabarka in north-western Tunisia (Vallebona, 1988). The structure of surnames in Carloforte is still rather peculiar, and very different from that of the other Sardinian municipalities (Vona et al, 1996;Caravello & Tasso, 2002b). Carbonia, another Sardinian municipality not far from Carloforte (Fig.…”
Section: Discussionmentioning
confidence: 84%
“…Other studies of the distribution of surnames in Sardinia established that they behave as neutral alleles (Zei et al, 1983a(Zei et al, ,b, 1986. Caravello and Tasso (2002) analyzed a database of surnames taken from the telephone directories of 12 Sardinian villages in the historical-geographical zone of Sulcis (Southwest Sardinia); they observed that villages founded relatively recently by a non-Sardinian population, e.g., Carloforte on the island of San Pietro (1738) and Calasetta on the island of Sant'Antioco (1770), had a peculiar distribution of surnames that reflected their specific history and culture, different from the other Sardinian villages analyzed. Another two villages, one founded in 1938 (Carbonia), the other geographically isolated (Teulada), were also distinct from the remaining eight villages in the Sulcis area (Caravello and Tasso, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Studies using surname analysis in Sardinia Vona, 1980, 1984;Zei et al, 1983aZei et al, ,b, 1986Wijsman et al, 1984;Piazza et al, 1985;Lucchetti et al, 1987;Guglielmino and Zei, 1996;Vona et al, 1996;Danubio, 1997;Caravello and Tasso, 2002) never clarified how the authors dealt with the problem of surname variants (Manconi, 1987;Pittau, 1990). In the present study, as in another in which the R ib values of 14 of the 16 villages examined here were analyzed for the periods 1800-1824and 1955-1974(Sanna et al, 2001, we considered last names with minimal spelling differences as the same surname (Kü chemann et al, 1979;Fuster, 1986;Pollitzer et al, 1988;Pettener, 1990;Rojas-Alvarado and Garza-Chapa, 1994;Madrigal and Ware, 1997;Sanna et al, 2001).…”
Section: Methodsmentioning
confidence: 99%
“…Surnames have proved to be useful for describing the population structure, and isonymy makes it possible to evaluate isolation and consanguinity (see the recent bibliography in Barrai et al, 13 Mathias et al, 14 RodriguezLarralde, 15 Lasker et al, 16 Sykes et al, 17 Manni et al, 18 Barrai et al, 19,20 Caravello et al, 21 Gagnon et al, 22 ). They are also frequently used as a tool to identify individuals' geographical origin (see the recent bibliography in Chan, 23 GarzaChapa et al, 24 De Silvesti and Guglielmino, 25 Pollock et al, 26 Jacobs and Landerdale, 27 Rudan, 28 Carta et al, 29 Brancatelli et al 30 ).…”
Section: Discussionmentioning
confidence: 99%